Longitudinal investigation of albumin-to-globulin ratio for human cancers demonstrates benefit in postoperative serial remeasurement - Zhenhui Li; Chunxia Li; Ruimin You; Yanli Li; Lizhu Liu; Hongjiang Pu; Ming Lei; Wenliang Li; Tao Zhang; Dingyun You (npj Precision Oncology)
Abstract Previous studies on serum albumin-to-globulin ratio (AGR) in human cancers were limited to its preoperative level, with postoperative serial AGR remeasurements ignored. In this study, 2844 CRC patients, 2267 NSCLC patients and 507 HCC patients who underwent curative resection were included. Postoperative AGR was a prognostic factor independent to preoperative AGR, performing a L shaped relation with OS. The 5-year OS rates for the persistently normal, normalized, lowered and persistently low perioperative AGR groups were 84.0%, 80.7%, 78.5% and 70.2%. Three longitudinal AGR trajectory groups were identified within 12 months after surgery. Compared with the normal-stable group, the adjusted HRs on OS for the rising-decreasing and decreasing-rising groups were 1.38 (95% CI: 1.13–1.68, P = 0.001) and 2.78 (95% CI: 2.30–3.36, P < 0.001). Similar results were observed for RFS. In conclusion, a routine follow-up of AGR in the postoperative surveillance will improve prognosis risk stratification of cancer patients.